Information System of Agricultural Land in Manduamas Sub District Tapanuli Tengah Regency. - Hotdi Briyan; Achwil Putra Munir; Ainun Rohana (Universitas Sumatera Utara, 2014)
Information System of Agricultural Land ( Rice) in Manduamas Sub District area was still done manually, so the storage, processing and delivery of information to be ineffective and inefficient. In the information management most the result were done by human role and took a relatively longer time. Moreover, the information seekers-and decision-makers also had difficulty in obtaining the data they need. Therefore, it is necessary to further develop of the information system. Web-based information system is considered to be a solution in order to access information faster, systematicaly and easy to use. For that a web-based information systems in the management of imformation system of agricultural land ( rice) in Manduamas sub district was designed. Agricultural land network information system was designed using PHP programming language, MySQL database and the method of system development life cycle (SDLC). The result was adynamic website that displays information and could interact with the user and was user friendly where the model user interface of the web was made to facilitate the user to use system properly. Keywords: Agricultural land, information system, Manduamas Sub district, rice, web.